Megiddo V : the 2004-2008 seasons - Finkelstein, Israel; Ussishkin, David; Cline, Eric H.; Adams, Matthew J. (Matthew Joel) (Monograph series (Makhon le-arkheʼologyah ʻa. sh. Sonyah u-Marḳo Nadler), 2013)
This 3-volume set is the third in the series of final publications of the Megiddo Expedition (see Megiddo III: The 1992-1996 Seasons, 2000; Megiddo IV: The 1998-2002 Seasons, 2006). It reports the finds in the 2004-2008 seasons, with several references to the campaign of 2010. The main topics dealt with are: a final account of the Early Bronze Age cultic compound; excavations of the late Iron I layer in Area H and the Late Bronze II-III layers in Area K; report on the investigation of Schumacher's Nordburg and Chamber f and its surroundings; the Late Bronze II-III, Iron I, and Iron IIA pottery of Megiddo; and a variety of microarchaeology studies.